Investigating The Awareness of Food Safety Among Buyers and Sellers in a Local Market - a Taste of Safety - Mahmood Shahidul Islam, Syed; Laskar, Nourjahan; Afrin, RPh. Sadia; Ahmed Mahed, RPh. Md. Rezwan; Musarrat, Zahra; Syrmos, Nikolaos (Riviera Publishing, 2023)
This research aims to assess the food safety knowledge among buyers and sellers in the city market, particularly in the post-pandemic context. The study focuses on understanding the extent to which individuals adhere to food safety and hygiene measures. The method used in this research is quantitative and conducted in the Mohammadpur city market, involving 101 buyers and 101 sellers selected for interviews. The research employed a structured questionnaire to gather information on participants' age, gender, level of education, and training on food safety. The results of the study indicate that a total of 202 participants, with an average age of 38.16 years, were involved. Gender distribution shows that the majority of buyers (72%) and sellers (87%) were male. The analysis demonstrates a significant relationship (p<0.001) between the level of education, training on food safety, and overall knowledge of food safety among buyers. This research implies the need for enhanced monitoring and regulation of activities conducted by food vendors to reduce potential risks and the transmission of foodborne illnesses. The implementation of regulations, promotion of hygienic practices, and food safety control measures are crucial steps to achieve this objective. Local authorities, with smooth execution of their duties, play a vital role in ensuring the effectiveness of these measures.